2017
DOI: 10.1007/978-1-4939-7033-9_34
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Effector Translocation using the TEM-1 Beta-Lactamase Reporter System

Abstract: Among the bacterial secretion systems, the Type III, IV, and VI secretion systems enable bacteria to secrete proteins directly into a target cell. This specific form of secretion, referred to as translocation, is essential for a number of pathogens to alter or kill targeted cells. The translocated proteins, called effector proteins, can directly interfere with the normal processes of the targeted cells, preventing elimination of pathogens and promoting their multiplication. The function of effector proteins va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Based on in silico predictions (as detailed in Materials and Methods), eight proteins of the novel strain L. pneumophila Pt/VFX2014 were selected as candidate Icm/Dot substrates: VFX03805, VFX05045, VFX05055, VFX06065, VFX09510, VFX12350, VFX13425 and VFX10045. To assess if these putative effectors were indeed delivered (i.e., translocated) into host cells by the Icm/Dot T4SS secretion system, we used the TEM-1 β-lactamase FRET-based reporter system ( Allombert et al., 2017 ). In this methodology, fusion proteins containing N-terminal TEM-1 are produced in L. pneumophila under the control of the Ptac IPTG-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in silico predictions (as detailed in Materials and Methods), eight proteins of the novel strain L. pneumophila Pt/VFX2014 were selected as candidate Icm/Dot substrates: VFX03805, VFX05045, VFX05055, VFX06065, VFX09510, VFX12350, VFX13425 and VFX10045. To assess if these putative effectors were indeed delivered (i.e., translocated) into host cells by the Icm/Dot T4SS secretion system, we used the TEM-1 β-lactamase FRET-based reporter system ( Allombert et al., 2017 ). In this methodology, fusion proteins containing N-terminal TEM-1 are produced in L. pneumophila under the control of the Ptac IPTG-inducible promoter.…”
Section: Resultsmentioning
confidence: 99%
“…Assays were performed essentially as described ( Allombert et al., 2017 ) using a LiveBLAzer™ FRET - B/G Loading CCF2/AM kit (Thermo Fisher Scientific). L. pneumophila strains harboring pXDC61 derivatives encoding TEM fusions to putative effectors (wildtype or dotA background; see Table S1 and S2) were grown in ACES-buffered yeast extract (AYE) supplemented with 1 mM IPTG and required antibiotics at 37°C overnight with agitation.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously reported that HipT Lp is translocated by L. pneumophila into its eukaryotic host via its Type IV secretion system (T4SS) (20), raising the intriguing possibility that it may represent a bacterial effector with an as-of-yet undefined host target. Notably, this hypothesis rests upon the report of a barely detectable signal in the TEM-1 translocation assay (21), in which TEM-1 β-lactamase is fused to a protein of interest and expressed in L. pneumophila cells infecting monolayers of differentiated U937 cells (29). Translocation is determined by monitoring emission from a fluorescent substrate within the host cells, which shifts from emitting green fluorescence to blue fluorescence upon cleavage of an internal beta-lactam ring by the TEM-1 fusion.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it should be noted that in previous work, HipT Lp was reported to be an effector based solely on a single qualitative micrograph demonstrating exceedingly low translocation efficiency (20, 21). Given that cytosolic proteins (such as FabI) can be translocated at low frequencies by the T4SS (29, 68), basal level of secretion should not be mistaken for functional translocation and warrants confirmation with orthologous methodologies. In the absence of this, exceeding a threshold ratio of quantified fluorescence should be the necessary standard for effector validation (29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…C-terminal effector-TEM1 β-lactamase (286 AAs, 32 kDa) fusions on the other hand allowed the analysis of Legionella pneumophila T4E and Enteropathogenic E. coli (EPEC) T3E translocation [88,89]. This system relies on the lipophilic esterified coumarin cephalosporin fluorescein (i.e., CCF2/4-AM) substrate that can easily permeate eukaryotic cell membranes.…”
Section: Enzymatic Andmentioning
confidence: 99%